A compreensão leitora de crianças de 4 e 5 anos em atividades de leitura literária e contação de histórias - Botelho, Melina Carvalho (2020)
The need to reflect and understand how reading and storytelling activities occur in school is prominent when considering reading as a social skill and a form of acquiring knowledge. Therefore, this study aims to identify the reading comprehension of children aged four and five years based on literary reading and storytelling activities while developing and applying these skills. The study also analyzed the children's speeches, highlighting reading comprehension. This qualitative research is conducted through a research–action, employing literary reading and storytelling activities with children aged four and five years. The activities took place in two reading situations: (i) when the teacher told stories to the students and (ii) when the teacher read the narratives of children's literature books. The activities were employed at two different times throughout the 2019 academic year. The moments were recorded in a field journal through the description and photographic images. We conducted conversations with the children, asked questions directed to the story's plot, and analyzed the impressions regarding the narratives' context after each reading activity. Thus, the investigative action was grounded on the following question: to what extent is it possible to identify the reading comprehension of children aged four and five years in literary reading and storytelling? The transcripts of the children's responses were based on the studies conducted by Freire (1989) and Cosson (2016), on reading and literary reading, Sisto (2007), regarding storytelling, and Vygotsky (2018), on conception and language, among other authors who discuss the theme. In conclusion, we highlight that reading comprehension is correlated to situations that integrate literary reading and pedagogical mediation. The product of this work was the literary reading and storytelling activities applied during the research.